Effects of aspirin on colon cancer using quantitative proteomic analysis - Zhang, Yan; Sun, Haitao; Ji, Yu; Nie, Fang; Wang, Rong; Han, Wei (Cancer pathogenesis and therapy, 2024)
Colon cancer is one of the most prevalent digestive cancers worldwide. Results of epidemiological, experimental, and clinical studies suggest that aspirin inhibits the development of colon cancer. This study aimed to systematically elucidate the molecular mechanisms by which aspirin prevents colon carcinogenesis. We determined the global protein expression profiles of colorectal cancer and aspirin-treated cells using quantitative proteomic analysis. We analyzed the proteomic results using bioinformatics (including differential proteins, protein annotation, Kyoto Encyclopedia of Genes and Genomes [KEGG] pathways, and protein–protein interaction [PPI] network). The viability of the colon cancer cell line and HT29 ​cells treated with aspirin was determined using the cell counting kit-8 assay. The differentially expressed proteins, such as p53 and cyclin-dependent kinase 1 (CDK1), were quantified using real-time polymerase chain reaction (PCR) and Western blotting. We measured cell cycle distribution and apoptosis in HT29 ​cells exposed to aspirin using fluorescence-activated cell sorting (FACS). We found that 552 proteins were significantly dysregulated, of which 208 and 334 were upregulated and downregulated, respectively, in colon cancer cells exposed to 10 ​mmol/L of aspirin (95% confidence interval [CI]: -1.269 to -0.106, P ​< ​0.05). Further gene enrichment analysis revealed that cell cycle-related proteins, such as p53 and CDK1, were significantly differentially expressed. Proteomic analysis showed that after 24 ​h of aspirin exposure, the level of p53 increased by 2.52-fold and CDK1 was downregulated to half that of the controls in HT29 ​cells (95% CI: -0.619 to -0.364, P ​< ​0.05). Real-time PCR and Western blotting results showed that p53 was upregulated (95%CI: -3.088 to -1.912, P ​< ​0.001) and CDK1 was significantly downregulated after aspirin exposure in colon cancer cells (95% CI: 0.576 to 1.045, P ​< ​0.05). We observed that aspirin promoted G1/S cell cycle arrest in HT29 ​cells. We confirmed that aspirin induces apoptosis in human HT29 colon cancer cells in a concentration-dependent manner. These results indicate that aspirin induces G1 arrest and apoptosis in colorectal cancer cells via the p53–CDK1 pathway. Aspirin may be a promising drug candidate for colon cancer prevention. Aspirin induces G1 arrest and apoptosis through the p53-Cyclin-dependent kinase 1 pathway as revealed by the protein changes observed in the proteomic analysis. [Display omitted] •Following exposure to 10 ​mmol/L of aspirin, 552 proteins were significantly dysregulated.•Cell cycle-related proteins, such as p53 and cyclin-dependent kinase 1 (CDK1), are the most differentially expressed proteins.•P53 and CDK1 were upregulated in colon cancer cells after exposure to aspirin.•Aspirin promotes G1/S arrest of cell cycle in HT29 ​cells.